Roles of MET in Cancer Development and Treatment - Jørgensen, Jan Trøst; Mollerup, Jens (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Understanding the impact of the hepatocyte growth factor receptor (MET) during cancer development, cancer growth, and cancer treatment is crucial to further improve biomarker development and cancer treatment options for patients' benefit. This reprint gives a snapshot of the current understanding of MET in lung and gastric cancer, describes promising new therapeutics, and emphasizes some of the challenges associated with their use.